Epidemiological study of type II diabetes mellitus in Kalutara District in Sri Lanka - Beneragama, .A.S.P (My University, 2002)
An epidemiological study was carried out to determine the prevalence of NIDDM and to develop a screening tool to detect NIDDM in the community setting using a cross-sectional descriptive study design. The study area was Kalutara district in Sri Lanka. A stratified cluster samples of 3000 between the ages of 30 to 64 years was enrolled for the prevalence study. The participation rate was 95.5 per cent. Important risk factors found were age more than 40 years, dryness of the mouth, constipation, presence of a family history of diabetes and nocturia. Screening tool was validated with the FPG value and the ROC analysis showed that the screening tool carries 53.3 per cent sensitivity, 60.8 per cent specificity and positive predictive value of 6 per cent. It is concluded that a questionnaire based on symptoms and risk factors is not suitable to screen for diabetes in the field setting